iDoor3D: immersive SketchUp learning of door construction in quantity surveying education - Md Dahlan, Farhan; Ab. Wahid, Abdul Muhaimin; Ali, Suhaila; Jenuwa, Norsyazwana; Abu Bakar, Norbaizura (2025)
Measurement work is a fundamental aspect of quantity surveying, particularly in taking of quantities for building elements such as doors. Traditional methods used in the Measurement of Construction Works II (QSA151) course rely heavily on textbooks with static illustrations and classroom hand sketches based ontwo-dimensional (2D) diagrams. While these may benefit students with strong spatial imagination, they pose challenges for those lacking such skills, resulting in reduced engagement difficulty in grasping practical applications. To address this, iDoor3D—an immersive SketchUp-based learning tool was developed to enhance visual learning through interactive three-dimensional (3D) animation, thereby improving students’ competency in measuring door elements. The tool integrates with the UFUTURE platform and YouTube for ease of access and navigation. This innovation aims to strengthen students’ drawing interpretation skills, foster active learning, and enhance technical practices through an engaging, interactive approach.